2013
DOI: 10.1371/journal.pone.0062034
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Interim Treatment Outcomes from the First Cohort of Multidrug-Resistant Tuberculosis Patients in Tanzania

Abstract: SettingKibong’oto National Tuberculosis Hospital (KNTH), Kilimanjaro, Tanzania.ObjectiveCharacterize the diagnostic process and interim treatment outcomes from patients treated for multidrug-resistant tuberculosis (MDR-TB) in Tanzania.DesignA retrospective cohort study was performed among all patients treated at KNTH for pulmonary MDR-TB between November 2009 and September 2011.ResultsSixty-one culture-positive MDR-TB patients initiated therapy, 60 (98%) with a prior history of TB treatment. Forty-one (67%) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
67
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(78 citation statements)
references
References 15 publications
10
67
1
Order By: Relevance
“…In a similarly treatment experienced population referred to KIDH for MDR-TB treatment, non-TB mycobacteria were found in~5% of patients. 6 Indeed, the patients that remained persistently smear positive in this current retreatment cohort and whose sputa were ultimately cultured and found to have MDR-TB may have already had amplified drug resistance on admission for retreatment. 13 Our findings emphasize the importance of rapid drug susceptibility testing in retreatment patients and caution against the reliance on sputum smear conversion as a proxy for effective treatment.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…In a similarly treatment experienced population referred to KIDH for MDR-TB treatment, non-TB mycobacteria were found in~5% of patients. 6 Indeed, the patients that remained persistently smear positive in this current retreatment cohort and whose sputa were ultimately cultured and found to have MDR-TB may have already had amplified drug resistance on admission for retreatment. 13 Our findings emphasize the importance of rapid drug susceptibility testing in retreatment patients and caution against the reliance on sputum smear conversion as a proxy for effective treatment.…”
mentioning
confidence: 90%
“…Although MDR-TB treatment began in Tanzania at KIDH in 2009, initially drug susceptibility testing was not routinely performed on retreatment patients given logistical constraints and specimen turnaround at the reference laboratory. 6 After 2013, molecular testing with either the Xpert MTB/RIF (Cepheid, Sunnyvale, CA) or the MTBDRplus (Hain Lifescience, Nehren, Germany) has been performed onsite.During the study period and excluding those with known MDR-TB, total 2,140 patients were admitted for TB treatment, of which 185 (8.6%) received a retreatment regimen ( …”
mentioning
confidence: 99%
“…The possible explanations rely partly on immunopathophysiology and hormonal mechanisms, and include increased cytokine release, such as TNF-∝ and production of gut hormone such as plasma peptin YY (PYY) [15,16]. Proper TB treatment may result in improvement of nutritional status [17][18][19]. A Cochrane review showed that both macro and micronutrient supplements during TB treatment had low to modest benefits in-terms of outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Multidrug-resistant (MDR)-TB treatment includes second-line drugs such as flouroquinolones, ethionamide and para-aminosalicylic acid, which can produce remarkable gastrointestinal intolerance [11,17]. Furthermore, patients with MDR-TB have often undergone prior treatment for TB without success and have consequently suffered from a more prolonged illness, which predisposes to malnutrition [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation